Effective suppression of machining-induced interlayer damage in machined holes of Al/CFRP stacks - Balázs Markó; Szilárd Seprős; Jinyang Xu; Norbert Geier (Composites Part C: Open Access)
Aluminium/carbon fibre reinforced polymer (Al/CFRP) composite stacks combine the high strength-to-weight ratio of the CFRP with the ductility and impact resistance of aluminium. Due to their excellent mechanical properties, Al/CFRP stacks are becoming increasingly popular in major industrial fields such as aerospace and automotive. However, mechanical machining of these materials, particularly at the interlayer regions, presents significant challenges, notably the formation of interlayer burrs. To address this issue, we introduce an innovative hole-making technology designed to minimise machining-induced interlayer burr formation. The novel technology integrates helical and spiral interpolation strategies to reduce axial force at the interlayer interfaces. We validated the efficiency of the novel technology through a series of machining experiments, employing a Central Composite Inscribed (CCI) experimental design. The experiments were performed on a three-axis CNC milling centre, with burr measurements obtained using a Keyence VR-5000 3D profilometer. Maximum burr heights were recorded along the hole contours at one-degree intervals. Our findings demonstrate a significant reduction (28 %) in interlayer burr formation in unidirectional carbon fibre-reinforced polymer (UD-CFRP) plates when utilising the proposed technique. These results suggest that our developed method is promising to improve machining quality in Al/CFRP stacks, meriting further investigation and development.